2019
DOI: 10.1017/s0047279419000515
|View full text |Cite
|
Sign up to set email alerts
|

Activation is not a panacea: active labour market policy, long-term unemployment and institutional complementarity

Abstract: Evaluation studies of active labour market policy show different activation measures generate contradictory results. In the present study, we argue that these contradictory results are due to the fact that the outcomes of activation measures depend on other institutions. The outcome measure in this study is the long-term unemployment rate. Two labour market institutions are of special interest in this context: namely, employment protection and unemployment benefits. Both institutions, depending on their design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Other studies have combined spending on public job creation and wage subsidies to private employers into one category (Benda, Koster, & Van Der Veen, 2019;Boone & van Ours, 2004. These studies find unfavourable effects of increased spending on this combined category on aggregate unemployment, but what drives the negative effects is therefore uncertain.…”
Section: Public Job Creationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have combined spending on public job creation and wage subsidies to private employers into one category (Benda, Koster, & Van Der Veen, 2019;Boone & van Ours, 2004. These studies find unfavourable effects of increased spending on this combined category on aggregate unemployment, but what drives the negative effects is therefore uncertain.…”
Section: Public Job Creationmentioning
confidence: 99%
“…While it is difficult to assess effects of job creation across various targets groups using macrolevel data, the macroeconomic evidence largely paints a similar picture as most evaluation studies, where spending on public job creation is found to be detrimental for, for example, employment rates of low‐skilled men and women (Abrassart, 2015). Other studies have combined spending on public job creation and wage subsidies to private employers into one category (Benda, Koster, & Van Der Veen, 2019; Boone & van Ours, 2004, 2009). These studies find unfavourable effects of increased spending on this combined category on aggregate unemployment, but what drives the negative effects is therefore uncertain.…”
Section: Disaggregating Almps—theoretical Effects and Previous Evidencementioning
confidence: 99%
“…Taking program context into account during design is also key. Benda, Koster, and Van Der Veen (2019) argue that the heterogeneity observed in impact evaluations of ALMPs is related to different employment protection and unemployment benefit regimes. Bergman et al (2019) show that a package of search assistance, landlord engagement, and short-term financial assistance was more successful in motivating households in low-income areas in the United States to move to high-opportunity areas than increasing the value of vouchers, in part because the specific needs of each family were addressed by the package of assistance.…”
Section: Such Potential Adverse Consequences Emphasize the Importance Of Getting Policy Design Rightmentioning
confidence: 99%
“…At the centre of social security policy for working age people is a perceived policy contradiction; that if the needs of people who are not in waged work are relieved, they will be disincentivised from taking waged work when it is available or incentivised to leave work for unemployment (Grover, 2016). Work incentives have been the focus of a range of policyrelated literature, including that concerned with social security policy (including Whiteford and Millar, 1994;Walker, 1998;Benda et al, 2020); labour market economics (for example, Spindler, 1975, 1979;Atkinson and Fleming, 1978;Kay, Norris and Warren, 1980;Britton, 1997) and that concerned with relationships between social policy and capitalist imperatives (for instance, Offe, 1984;Novak, 1988). While being embedded in different intellectual traditions, what unites these literatures is a concern with how social policy, and more specifically social security policy, might act to encourage or discourage people to commodify, to sell, their labour power.…”
Section: Social Security Policy and Work Incentivesmentioning
confidence: 99%